PERAN BAITUL MAAL WA TAMWIL DALAM MENGURANGI PRAKTIK RENTENIR DI ERA NEW NORMALI LIFE - Ratna (LA RIBA: Jurnal Perbankan Syariah, 2021)
The phenomenon at this time there are still many people who are entangled in loan sharks and online loans in the midst of the development of bank and non-bank financial institutions. Majority traders in the market, have limited capital so that when they have to increase capital in order to maintain business activities often still rely on the existence of loan sharks. Given this, the role of financial institutions becomes important to channel their credit to entrepreneurs who need additional capital, lending institutions are clearly needed by small entrepreneurs such as traders in the market. Baitul Maal Wa Tamwil (BMT) as one of the Islamic MicroFinance Institutions that can play a role in helping to increase small micro businesses. The method used in this study is qualitative with a descriptive approach to the role of BMT in reducing the practice of loan sharks in the new normal life era.